Does Money Matter for Inflation in Ghana? - Kovanen, Arto (IMF Working Papers; Working Paper ;, 2011)
Money has only limited information value for future inflation in Ghana over a typical monetary policy implementation horizon (four to eight quarters). On the other hand, currency depreciation and demand pressures (as measured by the output gap) are shown to be important predictors of future price changes. Inflation inertia is high and inflation expectations are largely based on backward-looking information, suggesting that inflation expectations are not well anchored and hence more is needed to strengthen the credibility of Ghana's inflation-targeting regime.1.